A Doctor among the Oglala Sioux Tribe : The Letters of Robert H. Ruby, 1953-1954 - Ruby, Robert H. (Book collections on Project MUSE., 2010)
"In 1953 young surgeon Robert H. Ruby began work as the chief medical officer at the hospital on the Pine Ridge Indian Reservation in South Dakota. He began writing almost daily to his sister, describing the Oglala Lakota people he served, his Bureau of Indian Affairs colleagues, and day-to-day life on the reservation."--Inside jacket